2013
DOI: 10.4067/s0718-95162013005000054
|View full text |Cite
|
Sign up to set email alerts
|

Effect of arginine pre-treatment on nickel accumulation and alleviation of the oxidative stress in Hyoscyamus niger

Abstract: Nickel is essential for many plant species to complete their life cycle but higher concentrations of this metal are toxic and may severely interfere with many physiological and biochemical processes of plants. In recent researches, either sodium nitroprusside (as nitric oxide donor) or exogenous polyamines were used to counteract the effect of heavy metal stress. In this research hyoscyamus plants were pre-treated with 10 and 20 µM Arg (as a precursor of NO or polyamines) and then plants were treated with 50 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…Thus, role of Arg has come into light due to its multiple metabolic fates. Apart from serving as a constituent of proteins, Arg is a precursor for biosynthesis of other substances like polyamines (PAs), agmatine and Pro, Glu and nitric oxide (NO) those play vital role in metal stress tolerance (Liu et al, 2006 ; Nasibi et al, 2013 ). Arg biosynthesis in plant occurs through ornithine (Orn) which comes from few steps conversion of Glu involving five enzymes (Verma and Zhang, 1999 ).…”
Section: Non-thiol Compounds and Metal(loid)-chelationmentioning
confidence: 99%
“…Thus, role of Arg has come into light due to its multiple metabolic fates. Apart from serving as a constituent of proteins, Arg is a precursor for biosynthesis of other substances like polyamines (PAs), agmatine and Pro, Glu and nitric oxide (NO) those play vital role in metal stress tolerance (Liu et al, 2006 ; Nasibi et al, 2013 ). Arg biosynthesis in plant occurs through ornithine (Orn) which comes from few steps conversion of Glu involving five enzymes (Verma and Zhang, 1999 ).…”
Section: Non-thiol Compounds and Metal(loid)-chelationmentioning
confidence: 99%
“…Nasibi et al [61] in their study on Hyocyamus niger found that Ni 2+ showed decrease in chlorophyll a and total chlorophyll which was further maintained/recovered by Arginine pretreatment in Ni 2+ stressed plants. Pietrini et al [62] in a study on Amaranthus paniculatus L. reported that the exposure of plants to increasing Ni 2+ in the growth solution caused a significant increase in free polyamine content in roots and leaves of test plant at 25 µM NiCl 2 , whereas a decrease in the PAs (Spermidine and Spermine) content of plants at higher Ni 2+ concentrations.…”
Section: Physical Barriersmentioning
confidence: 97%
“…Asparagine has been linked to glutamine and arginine as the major nitrogen transporters in plants. 36 Asparagine and glutamine are known to be present in high concentrations in seeds of plants and this is reflected in the concentrations present in B. coddii seeds.…”
Section: Amino Acids In B Coddiimentioning
confidence: 99%